Anti-inflammatory activity of Indonesian nutmeg seeds (Myristica fragrans Houtt): A topical gel formulation - Azis Ikhsanudin; Lolita Lolita; Daniar Dyanas Rais (International Journal of Public Health Science (IJPHS), 2021)
Herbal medicines have been shown as anti-inflammatory with potentially lesser side effects. The active compound of nutmeg seed is proven to accelerate the healing process of inflammation. This study aimed to evaluate the gel formulation of Indonesian nutmeg (Myristica fragrans Houtt) seed extract for anti-inflammatory activity. A true experimental post test only with control group design was used in this study. The gel was formulated with various concentrations of nutmeg seed extract, namely formulations F1 (0%), F2 (2%), F3 (4%), F4 (8 %), and F5 (12%). Analysis of variance (ANOVA) followed by the least significant difference (LSD) methods were performed with SPSS version 22. The results showed that all formulas had an opaque physical appearance, brownish-yellow color, soft texture, and aromatic odor. The increase of extract concentration in gel formula will affect the adhesion and spreadability. F5 showed the highest anti-inflammatory activity compared to other groups. This formula was generally identified as having a good physical appearance, homogeneity, and stability with a pH value of 6.16±0.24, adhesiveness of 51.12±0.15 sec, and a spreadability of 19.54±0.12 cm2. Therefore, Indonesian nutmeg has the potential to be well-acceptable as a candidate for topical anti-inflammatory agents in global health benefits.